Community Based Economic Empowerment and Educational Consciousness Raising Through Participatory Organizing: A Case Study from Randuagung Village, Gresik - Risallah, Fiqih; Aries Kurniawan; Beni Dwi Komara; Putra Panji Respati (Kontribusia : Research Dissemination for Community Development, 2026)
Community service engagement in Randuagung Village, Kebomas District, Gresik, East Java, was designed to enhance the socio-economic capacity of residents who predominantly depend on agricultural and small-scale industrial sectors. The primary challenges identified were low business productivity, limited access to education—affecting 19.77% of the population with no formal schooling—and the absence of critical awareness regarding education and innovation. The methodology employed a community organizing approach combined with skills training, technical mentoring, and marketing network development. The program engaged microentrepreneurs, farmers, youth, and women as active participants. Results demonstrated increased community participation in business management, adoption of appropriate technology, and the establishment of Kelompok Usaha Bersama or KUB (Joint Business Groups) that strengthened solidarity and collaborative practices. The engagement successfully catalyzed sustainable social transformation, fostered economic independence, and cultivated heightened consciousness regarding the importance of education and innovation among village residents.